2015
DOI: 10.3390/antiox4020373
|View full text |Cite
|
Sign up to set email alerts
|

Food Inhibits the Oral Bioavailability of the Major Green Tea Antioxidant Epigallocatechin Gallate in Humans

Abstract: The bioavailability of the most abundant and most active green tea antioxidant, epigallocatechin gallate (EGCG) remains uncertain. Therefore, the systemic absorption of EGCG was tested in healthy fasted humans. It was administered as capsules with water or with a light breakfast, or when incorporated within a strawberry sorbet. The results for plasma EGCG clearly revealed that taking EGCG capsules without food was better; the AUC was 2.7 and 3.9 times higher than when EGCG capsules were taken with a light brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
89
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 50 publications
6
89
0
1
Order By: Relevance
“…The studies outlined in this review have demonstrated some of the putative cardiovascular protective properties that GTCs may have on the lowering of body weight, arterial blood pressure, and plasma abnormalities in biomarkers commonly seen in individuals who are prone to developing a serious CVD-related illness in the future. Beneficial effects were observed when GTE was supplemented at levels between 300 and 1500 mg/day (total GTCs 208-1344 mg/day), roughly in line with previous literature, which had suggested that 540 mg of pure EGCG (between 5 and 10 cups of green tea [39]) was the optimal daily requirement for prevention of CVD risk factors [40]. Furthermore, the duration of the studies was also considered in the present systematic review, as significant sustained lowering of the CVD risk biomarkers were more likely to be seen in studies conducted over at least 12 weeks of supplementation [9][10][11][12][13][14][15].…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The studies outlined in this review have demonstrated some of the putative cardiovascular protective properties that GTCs may have on the lowering of body weight, arterial blood pressure, and plasma abnormalities in biomarkers commonly seen in individuals who are prone to developing a serious CVD-related illness in the future. Beneficial effects were observed when GTE was supplemented at levels between 300 and 1500 mg/day (total GTCs 208-1344 mg/day), roughly in line with previous literature, which had suggested that 540 mg of pure EGCG (between 5 and 10 cups of green tea [39]) was the optimal daily requirement for prevention of CVD risk factors [40]. Furthermore, the duration of the studies was also considered in the present systematic review, as significant sustained lowering of the CVD risk biomarkers were more likely to be seen in studies conducted over at least 12 weeks of supplementation [9][10][11][12][13][14][15].…”
Section: Discussionsupporting
confidence: 72%
“…In addition, GTCs are expected to prevent this vascular inflammation by suppressing leukocyte adhesion ability to the endothelium, thereby indicating the potential to inhibit progression of atherosclerotic lesions and thrombogenesis [38] However, despite these findings, the reviewed studies showed varying degrees of hypocholesterolemic and hypolipidemic activity in participants, with some studies indicating insignificant change for both parameters in the group supplemented with GTCs [11,12,14]. This finding is possibly attributed to the differing health conditions and statuses of the participants recruited, differences in study designs [1], and the effect of food consumption on catechins systemic absorption [39].…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…The product formulation or food matrix also has a number of physical effects that could affect bioavailability. A study in much larger molecular weight green tea polyphenol epigallocatechin gallate has identified that its systemic absorption was reduced when this catechin ingested with food or if it is imbedded in the food matrix if compared to the pure product (Naumovski et al, 2015). From the studies reported, the quality and concentrations of the cocoa powder constituents used were not always reported including its ability to be dispersed in the medium (typically water) (Fogliano et al, 2011).…”
Section: Postabsorption Effects Of Sugar On Cocoa Bioactivitymentioning
confidence: 99%
“…Genetic predisposition [44] and nutrition patterns interacting with polyphenol absorption [40,45] are among the factors that were postulated to contribute to the interindividual variations. The microbiome hypothesis seeks to explain the varying effects of green tea administration through the impact of the gut microbiome [28,42].…”
Section: Introductionmentioning
confidence: 99%